Physiological profiles of elite wheelchair basketball players in preparation for the 2000 Paralympic Games - Goosey-Tolfrey, V. L. (Adapted Physical Activity Quarterly, 2005)
The purpose of this study was to examine the physiological changes in elite wheelchair basketball players leading up to the 2000 Paralympics. Twelve male players attended regular physiological assessments on six occasions; averaged data of two sessions for each year were used. Physiological measures included body mass, skinfold measurements, peak oxygen uptake and peak power obtained during maximal sprinting. VO2peak significantly increased from 2.65 to 2.83 L·min-1 prior to the Paralympics. Training had little influence on the anthropometric measurements or maximal sprinting data. In conclusion, the GB wheelchair basketball players appeared to have high levels of aerobic and anaerobic fitness. The longitudinal physiological profiles leading to the 2000 Paralympics suggest that players improved their aerobic base while maintaining other fitness prerequisites.